1996
DOI: 10.1007/bf00121681
|View full text |Cite
|
Sign up to set email alerts
|

Machine scheduling with an availability constraint

Abstract: Most literature in scheduling assumes that machines are available simultaneously at all times. However, this availability may not be true in real industry settings. In this paper, we assume that the machine may not always be available. This happens often in the industry due to a machine breakdown (stochastic) or preventive maintenance (deterministic) during the scheduling period. We study the scheduling problem under this general situation and for the deterministic case.We discuss various performance measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
230
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 358 publications
(232 citation statements)
references
References 14 publications
0
230
0
2
Order By: Relevance
“…Lee [2] also showed that if the Moore and Hodgson algorithm was used for solving the problem 1, ℎ 1 || ∑ , the inequality ( ) ≤ * ( ) + 1 would always be true, in which ( ) denotes the number of tardy jobs obtained by the Moore and Hodgson algorithm and * ( ) denotes the optimal number of tardy jobs.…”
Section: Theorems Of the Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…Lee [2] also showed that if the Moore and Hodgson algorithm was used for solving the problem 1, ℎ 1 || ∑ , the inequality ( ) ≤ * ( ) + 1 would always be true, in which ( ) denotes the number of tardy jobs obtained by the Moore and Hodgson algorithm and * ( ) denotes the optimal number of tardy jobs.…”
Section: Theorems Of the Problemmentioning
confidence: 99%
“…Go to Step 2. It is necessary to note that Lee [2] did not propose any procedure to solve the problem optimally. From the above considerations, we can conclude the following corollary.…”
Section: Theorems Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee [12] studies the deterministic machine availability constraint problem with di erent performance measures, including makespan, total weighted completion time, maximum lateness and number of tardy jobs, for single machine and parallel machines situations. In each case, he either provides a polynomial exact algorithm to solve the problem, or proves that the problem is NP-hard.…”
Section: Problem Statementmentioning
confidence: 99%